2017
DOI: 10.1007/s00402-017-2626-x
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphotypes of the varus and valgus knee

Abstract: Level IV study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(87 citation statements)
references
References 35 publications
3
83
0
1
Order By: Relevance
“…Also, preoperative pain and functional status, as measured by PROs, have been shown to predict pain and functional ability after TKAs [12,13]. There are some reports focused on radiological factors of the knee, such as bone morphology, knee alignment and osteophytes, but they evaluate only the variation of radiographic factors themselves or the relationships between the factors and the progression of osteoarthritis [14][15][16][17][18]. Thus far, there is little information regarding the influence of preoperative radiological differences on PROs after TKA.…”
Section: Introductionmentioning
confidence: 99%
“…Also, preoperative pain and functional status, as measured by PROs, have been shown to predict pain and functional ability after TKAs [12,13]. There are some reports focused on radiological factors of the knee, such as bone morphology, knee alignment and osteophytes, but they evaluate only the variation of radiographic factors themselves or the relationships between the factors and the progression of osteoarthritis [14][15][16][17][18]. Thus far, there is little information regarding the influence of preoperative radiological differences on PROs after TKA.…”
Section: Introductionmentioning
confidence: 99%
“…Complicating this goal is that patients presenting with osteoarthritis often have either varus or valgus deformity. Significant deformities are more difficult to correct to neutral mechanical alignment if conventional instrumentation is used [ 37 , 38 ]. Depending on the degree of deformity, the surgical technique, and the choice of implant, the amount of necessary constraint might differ [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that bone morphology in varus and valgus deformity is different before and after OA, and that perpendicular cuts to mechanical axes do not necessarily lead to a neutral mechanical axis. Deformities over 10° usually had an extra-articular component, thus correction to neutral alignment with conventional instruments might not be sufficient to compensate for femoral bowing or extra-articular deformity [ 38 ]. The JOURNEY™ II BCS provides more mobility in the lateral compartment than other total knee systems provide, to replicate normal knee kinematics.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative demographic data and clinical information were collected, including age, sex, body mass index (BMI), side of the operation, Charlson Comorbidity Index (CCI), use of walking assisting device, preoperative alignment, range of motion (ROM), and modified knee score. Alignment of the knee was determined using hip knee axis (HKA), and alignment was classified as varus alignment if the HKA was <178 o , and valgus alignment if the HKA was >182 o [ 13 ]. Our primary outcome of interest was the performance-based tests: Timed Up and Go (TUG) test and 2-min walk test (2MWT).…”
Section: Methodsmentioning
confidence: 99%